PREDIKTOR YANG MEMPENGARUHI PELAKU DAN KORBAN PERUNDUNGAN MAYA - Faiqoh, Faiqoh (JURNAL PSIKOLOGI INSIGHT, 2019)
This study was aimed to predict cyber-bullying by self esteem, academic performance, and lonliness. The participants of the study were 313 junior high school students that selected by nonprobability sampling technique. This study used eight instruments that were validated by confirmatory factor analysis and was analyzed by multiple regression. The results of the study were significant prediction of peer-related loneliness, affective performance, and gender to cyber-bulliers and significant preditctions to cyber-bullying victims by peer-related loneliness, in affective performance